Next QUANTUM COMPUTERS and their SPEEDS - puccini, Antonio (European Journal of Applied Sciences, 2021)
As known, the Quantum Computer represents the most coveted and promising tool for transmitting information in the near future. Thus, with the next use of Quantum Computers (QCs), instead of current computers, the means of transmitting information will be replaced: in fact we will pass from electrons and bit, to photons and quantum bit. So the main element, that is the essential and indispensable tool to make the next QCs, will be represented by the photon, that is by the electromagnetic signal. These signals, as we know, are not all the same, but they differ in a wide range, based on their wavelength, on their energy, or even on their momentum (p). In short, the main task of our work is to ascertain whether, in this context, the photons with different frequencies transmit the information at the same speed, or not!